Waste Management in Wonogiri Regency: Strategy Towards Sustainable Environmental Management - Janah, Sulatin Baeti; Husodo, Jadmiko Anom (Journal of Law, Politic and Humanities, 2025)
Waste is one of the main issues in sustainable development, especially in areas with increasing population growth rates. Wonogiri Regency through Regional Regulation Number 11 of 2018 has regulated waste management as part of efforts to create a healthy environment. This study aims to examine waste management in Wonogiri Regency in realizing a strategy towards a sustainable environment. The theory used in this study is the implementation theory of George Edwards III. The method used in this study is descriptive qualitative with the research subjects being policy implementers who play a role in waste management in Wonogiri Regency. The results of the study show that although the Regional Regulation of Wonogiri Regency has provided an adequate legal framework, the challenges of implementation in the field are still quite large, especially in terms of community participation and infrastructure support.